The relationship between electricity consumption, electricity price and economic growth in Turkey: 1984-2007 - AytaÇ, Deniz; Güran, Mehmet Cahit (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
The experience of economic development and industrialization of countries has revealed the increasing importance of the energy factor, which is a basic production input in the production process. Empirical studies have shown that a positive causality relation exists between the energy consumption and economic growth performance of countries. Another variable the effects of which need to be studied alongside the relation between these two variables, is energy price. In this study, the Granger causality between energy price, energy consumption and economic growth of Turkey is examined for the 1987-2007 period using a VAR model and quarterly data. The results indicate that a bidirectional causality relation appears to exist between electricity consumption and GDP, and that there is a causality relation that runs from real GDP to electricity price
Argumenta Oeconomica, 2011, Nr 2 (27), s. 101-124
Keywords: energy consumption; energy price; economic growth; energia; electric power